Role of Municipal Finances in Modern Economy - Ivanova O. E., Parkhomenko N. V. (Law, Economics and Management, 2021)
Currently, Russia is undergoing transformational processes that require a revision of the understanding of the nature and role of municipal Finance in the modern economy. The article presents the definitional certainty of the category "municipal Finance", scientific approaches to the structure and composition of municipal Finance, sources of financial resources of the municipality, as well as elements of municipal Finance. It is concluded that the role of municipal Finance in the modern economy is predetermined by the challenges associated with economic instability, budget deficit, on the other hand, the prerequisites for revising the current approach associated with expanding the understanding of the role of the population, local self-government bodies in the process of economic development of territories
Keywords: финансовая система; financial system; децентрализованные денежные фонды; источники финансовых ресурсов; муниципальные финансы; финансы муниципальных образований; централизованные денежные фонды; decentralized monetary funds; sources of financial resources; municipal Finance; centralized monetary funds